Aloe vera Effervescent Tablet Formulation: Comparation Study of Acid-Alkali-Aloe Powder and Maltodextrin Concentration - Kasmawarni, Kasmawarni; Utomo, Pramono Putro (Biopropal Industri, 2010)
The research on The Application of Effervescent Technology of Aloe vera as Functional Drink has been done. The objectives were to obtain effrvescent tablet prefered by the panelist as well as nutritious as aloe vera-based functional food also to obtain appropriate formula resulting good quality of effervescent tablet. Formulation of effervescent tablet with treatments of maltodextrin concentration were done. The result showed that the best formulas of aloe vera effervescent tablet were aloe vera concentration 33%, maltodextrin 7,5%, acid-karbonat total 43%, sorbitol 5%, sukralose 3 % and Polyethylenglicol 8000 %.